Parallel variational iterative linear solvers - Čiegis, Raimondas; Čiegis, Remigijus; Jakušev, Alexander; Šaltenienė, Gailė (Mathematical Modelling and Analysis, 2007)
In this work we consider parallel variational algorithms for solution of linear systems. Theoretical analysis explains the superlinear convergence rate for two step gradient descent method. A new modification of the algorithm is proposed. Results of computational experiments are given for a linear system of equations approximating 3D elliptic boundary value problem. All algorithms are implemented using parallel array object tool ParSol, then a parallel algorithm follows semi‐automatically from the serial one. Results of the scalability analysis are presented and the efficiency of the presented parallel algorithm is investigated experimentally. First Published Online: 14 Oct 2010